The Effect of Digital Literacy Capabilities and Self-Regulation on the Student's Creativity in Online Physics Teaching - Syefrinando, B.; Sukarno, S.; Ariawijaya, M.; Nasukha, A. (Jurnal Pendidikan IPA Indonesia, 2022)
This research intends to investigate the effect of digital literacy skills and self-regulation on student creativity in online physics learning practices. The approach used in this research is quantitative, with the data collection technique being a survey model. The research design used a quasi-experimental model with a pretest and posttest design. The samples were physics education students of UIN Sulthan Thaha Saifuddin Jambi, with a total sample of 42 students. Data analysis was conducted through several stages, namely: a) the first stage was to analyze category classification, namely classifying student abilities into very good category (A), good category (B), sufficient category (C), and poor category (D), based on the score of the measurement results of the three variables; b) the second stage is to test the correlation between variables. Correlation data analysis was performed with SPSS 25 software. Based on the data and discussions that have been carried out, it can be concluded that there is an influence between digital literacy skills and self-regulation on students' creativity in online physics learning practices. The effect of digital literacy skills on student creativity in carrying out online physics learning practices is 85%, while self-regulation has an effect of 78%. Both variables together affect students' creativity in learning physics online by 74%.